Primary Tumor Fluorine‐18 Fluorodeoxydglucose (18F‐FDG) Is Associated With Cancer-Associated Weight Loss in Non-Small Cell Lung Cancer (NSCLC) and Portends Worse Survival - Olaechea, Santiago; Gannavarapu, Bhavani S.; Alvarez, Christian; Gilmore, Anne; Sarver, Brandon; Xie, Donglu; Infante, Rodney; Iyengar, Puneeth (Frontiers in Oncology, 2022)
Aim To investigate the diagnostic potential of and associations between tumor 18F‐FDG uptake on PET imaging and cancer-associated weight loss. Methods 774 non-small cell lung cancer (NSCLC) patients with pre-treatment PET evaluated between 2006 and 2014 were identified. Using the international validated definition of cachexia, the presence of clinically significant pretreatment cancer-associated weight loss (WL) was retrospectively determined. Maximum Standardized Uptake Value (SUVMax) of 18F‐FDG was recorded and dichotomized based on 3 experimental cutpoints for survival analyses. Each SUVMax cutpoint prioritized either survival differences, total cohort comparison sample sizes, or sample size by stage. Patient outcomes and associations between SUVMax and cancer-associated weight loss were assessed by multivariate, categorical, and survival analyses. Results Patients were found to have an increased likelihood of having WL at diagnosis associated with increasing primary tumor SUVMax after controlling for potentially confounding patient and tumor characteristics on multivariate logistic regression (OR 1.038; 95% CI: 1.012, 1.064; P=0.0037). After stratifying the cohort by WL and dichotomized SUVMax, both factors were found to be relevant in predicting survival outcomes when the alternative variable was constant. Of note, the most striking survival differences contributed by WL status occurred in high SUVMax groups, where the presence of WL predicted a median survival time detriment of up to 10 months, significant regardless of cutpoint determination method applied to categorize high SUVMax patients. SUVMax classification was found to be most consistently relevant in both WL and no WL groups. Conclusions The significant positive association between significant pretreatment cancer-associated weight loss and primary tumor SUVMax underscores increased glucose uptake as a component of catabolic tumor phenotypes. This substantiates 18F‐FDG PET analysis as a prospective tool for assessment of cancer-associated weight loss and corresponding survival outcomes. Furthermore, the survival differences observed between WL groups across multiple SUVMax classifications supports the importance of weight loss monitoring in oncologic workups. Weight loss in the setting of NSCLCs with higher metabolic activity as determined by 18F‐FDG PET signal should encourage more aggressive and earlier palliative care interventions.